Long-term stability of isolated advancement genioplasty, and influence of associated risk factors: A systematic review. Issue 4 (April 2021) - Janssens, E; Shujaat, S; Shaheen, E; Politis, C; Jacobs, R
Abstract: The aim of this review was to investigate the skeletal and soft tissue stability of isolated advancement genioplasty after more than 1 year, and to observe the influence of associated risk factors. A literature search was performed on PubMed, Web of Science, Embase, ScienceDirect, and Cochrane. Only studies with at least 10 patients who underwent an isolated advancement genioplasty, and with a follow-up period of at least 1 year, were included. Of the 2224 records initially identified, eight articles met the eligibility criteria. The mean age of the total study population was 23 years and ranged from 19.1 to 26.5 years in the individual studies. The average surgical advancement at pogonion was 8.2 mm and ranged from 6.2 to 11.7 mm in the individual studies. After 1 year, the horizontal hard tissue relapse at the level of pogonion varied from 0.1 to 2.1 mm. In two studies, this was reported as statistically significant. Regarding the soft tissue, the horizontal relapse varied from 0.3 to 2.9 mm, which was also considered statistically significant in two studies. Isolated advancement genioplasty was found to be a predictable and stable orthognathic procedure in the sagittal plane at both soft and hard tissue levels. The amount of relapse was not associated with the fixation method or with the amount of surgical advancement.